Internal and External Factors for Sustainable Tourism Village Development: A Case Study of Bukit Sinyonya Tourism Village, Pandeglang Regency - Lulu Larasati; Kadek Wiweka (QISTINA: Jurnal Multidisiplin Indonesia, 2026)
Purpose of the study: This study aims to analyze internal and external factors as well as development strategies for Bukit Sinyonya Tourism Village as a sustainable tourism destination. Research Methods: This research applies a case study method with a qualitative approach. Data were collected through observation, interviews, and documentation. SWOT analysis was used to identify strengths, weaknesses, opportunities, and threats. Implications: The findings provide practical recommendations for stakeholders to strengthen sustainable tourism development in Pandeglang and can serve as a reference for other tourism villages with similar characteristics.